Time from last chemotherapy to death and its correlation with the end of life care in a referral hospital - Syed Mustafa Karim; Jamal Zekri; Ehab Abdelghany; Reyad Dada; Husna Munsoor; Imran Ahmad (Indian Journal of Medical and Paediatric Oncology)
Background: A substantial number of cancer patients receive chemotherapy until the end of life (EoL). Various factors have been shown to be associated with receipt of chemotherapy until near death. In this study, we determine our average time from last chemotherapy to death (TLCD) and explore different factors that may be associated with decreased TLCD. Materials and Methods: A retrospective review of medical records of adult cancer patients who received chemotherapy during their illness and died in our hospital between January 2010 and January 2012 was conducted. Chi-square test and t-test were used to examine the correlation between selected factors and use of chemotherapy within 60 days of death. Multivariate analysis was used to test independent significance of factors testing positive in univariate analysis. Kaplan-Meier method was used to perform survival analysis. Results: Of the 115 cancer patients who died in the hospital, 41 (35.6%) had TLCD of 60 days or less. Patients with better performance status and those dying under medical oncology service were more likely to be in this group of patients. Univariate analysis showed that these patients were less likely to have palliative care involvement, were more likely to die of treatment related causes, and more likely to have died in the Intensive Care Unit. Multivariate analysis confirmed lack of palliative care involvement and better performance status as independent factors for TLCD less than 60 days. Survival analyses showed that patients with palliative care involvement and those dying under palliative care service were likely to have significantly longer TLCD. Conclusions: Cancer patients who have no involvement of palliative care team in their management tend to receive chemotherapy near the EoL, have more aggressive EoL care, and have higher risk of dying die from treatment related complications. Palliative care should be involved early in the care of cancer patients.